Raton's Glenn Karlin set to perform benefit concert - Williams, Jess (Raton Range Raton, NM, 1987)
This article is about Glenn Karlin a 1966 Raton High School graduate and semi-professional singer to give a benefit concert for the Raton Humane Society.
Newspaper article + Photograph of Glenn Karlin
Mater List Item # 17
File location is in the Raton File Cabinet
Keywords: Karlin, Glenn; Hogg, LaNisa; McAllister, Linda; Bonahoom, Barbara; Raton High School; Musician History; Singing Veterinary; Benefit Concerts; Live Performances; Raton, New Mexico; Taos, New Mexico